Relação entre o comportamento alimentar e os parâmetros socioeconômicos e demográficos e o estado nutricional de pessoas com diabetes mellitus tipo 2 atendidas em um hospital de referência em belém, pa - ARAÚJO, Bruno Corrêa (2024)
Type 2 diabetes mellitus (DM2) is characterized by a condition of sustained hyperglycemia and is strongly associated with an increase in overweight and obesity in the population. It is therefore essential to know the nutritional status of these individuals, as it allows lifestyle changes and adaptation to dietary treatment to be monitored. In addition, nutritional management should not only be prescriptive, but should also be more subjective, placing the individual at the center of care. With this in mind, this study aims to test the correlation between eating behavior and socioeconomic, demographic and anthropometric parameters in people with DM2. This is a cross-sectional, descriptive and analytical study carried out between August and October 2023 at the João de Barros Barreto University Hospital. Socioeconomic, demographic and anthropometric data were collected (weight and height, to calculate body mass index - BMI; arm circumference - ACB; and neck circumference - NC). The Three Factor Eating Questionnaire (TFEQ-R21) was used to assess eating behavior. The study was approved by the Research Ethics Committee (opinion number 6.087.34). Statistical Package for Social Science software, version 21, was used for the statistical analysis, considering a statistical significance level of p<0.05. A total of 44 individuals were assessed with a mean age of 55.41 (± 6.41) years, the majority of whom were female (72.70%). With regard to anthropometry, most of the participants were classified as overweight according to BMI (43.20%; n=19), eutrophic according to WC adequacy (72.70%) and 86.4% had cardiovascular risk according to WC. Correlations were found between emotional eating behavior and weight (r²=0.326, p=0.031), BMI (r²=0.436, p=0.003) and %CB (r²=0.403, p=0.007); as well as a correlation between emotional eating and schooling (r²=0.324, p=0.032). There were also inverse correlations between age and the domains of cognitive restriction (r²=-0.350; p=0.020), emotional eating (r²=-0.304; p=0.045) and uncontrolled eating (r²=-0.398; p= 0.007). It can be concluded that eating behavior in patients with DM2 is influenced by a number of factors, including anthropometric characteristics, age and level of education. Understanding these relationships can be beneficial, since adapted to the individual needs of patients, they can promote healthy eating behaviors and adequate glycemic control.